The characteristics of foreign bodies aspirated by children across different continents: A comparative review. Issue 2 (28th November 2022) - Parvar, Seyedeh Yasamin; Sarasyabi, Mohammad Sharifi; Moslehi, Mohammad Ashkan; Priftis, Kostas N.; Cutrera, Renato; Chen, Meng; Lili, Zhong; Gonuguntla, Hari K.; Joseph, Tinku; Alajmi, Mohsen; Alshammari, Salman; Singh, Varinder; et al.
Abstract: Background: Foreign body aspiration (FBA) is a common issue in pediatric emergencies, with regional variations. Various cultures and foods, parents' and physicians' inadequate experience, and lack of bronchoscopy equipment are some attributable factors in the regional variation of FBA. Aim: To more accurately represent the demographic characteristics of aspirated foreign bodies (FBs) across various continents, this review attempted to provide organized information based on the reviewed articles. Methodology: A search was conducted in PubMed/PubMed Central, EMBASE, and google scholar. From the 36 included articles, information on age, gender, bronchoscopy type, type of FB, location, history of choking, and time elapsed between aspiration and admission were extracted. Results: A total of 14, 469 cases were evaluated. According to the findings, children under two accounted for more than 75% of FBAs. Nuts and seeds were the most common FBs in most countries, whereas plastic and metal objects had higher rates in Brazil, and calcified objects were more prevalent in Thailand. The right bronchus was the most frequent location, and rigid bronchoscopy was the most often utilized type of bronchoscope. In addition, a significant percentage of patients were referred to the emergency rooms in the first 12−24 h following the aspiration incident. Moreover, Asian patients reported more choking history, and Europeans had fewer witnesses of FBA. Conclusions: There is a lack of standardized reporting systems and organized guidelines in pediatric FBA. To select the ideal time for endoscopies and create educational programs, a collaboration between experienced researchers, pediatric pulmonologists, radiologists, and otolaryngologists is required.